Formulation of 70% Ethanol Extract Cream of Ketapang Leaf (Terminalia catappa L.) and Efficacy Test for Cut Wound in Mice (Mus muscullus) - Nurain Thomas; Fika Nuzul Ramadhani; Nur Rasdianah; Mohamad Aprianto Paneo; Kadaria Toana (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
A laceration (vulnus scissum) is characterized by straight, regular wound edges, typically resulting from sharp object trauma. Ketapang leaves (Terminalia catappa L.) contain bioactive compounds, including flavonoids, saponins, tannins, sterols, alkaloids, and terpenoids, which possess anti-inflammatory properties and the potential to accelerate wound recovery. This study aimed to evaluate the effectiveness of an extract cream derived from T. catappa leaves on laceration healing in mice (Mus musculus). The extract was obtained via maceration using 70% ethanol, followed by phytochemical screening. The cream base was optimized to meet pharmaceutical standards, with evaluations encompassing organoleptic properties, pH, dispersibility, adhesion, viscosity, and freeze-thaw stability. Three formulations were developed with varying extract concentrations: F1 (15%), F2 (20%), and F3 (25%). The in vivo efficacy test involved five groups of mice. Results indicated that all three formulations met the criteria for physical stability. In terms of healing duration, the negative control group required 21 days, while the positive control group achieved healing in 10 days. Among the treatment groups, F1 (15%) and F2 (20%) showed healing times of 18 and 16 days, respectively. Notably, F3 (25%) exhibited the highest efficacy with a healing time of 10 days, comparable to the positive control. Statistical analysis using One-Way ANOVA confirmed these findings with a p-value < 0.05.